CUSTOMER RELATIONSHIP MANAGEMENT IN FINANCIAL SERVICES: A STUDY ON SOME SELECTED PRIVATE COMMERCIAL BANKS IN BANGLADESH - Iqbal, Mohammed Masum (International Journal of Psychosocial Rehabilitation, 2020)
The financial service industry is facing immense competition across the world and, in Bangladesh, the scenario is not different. The banks in Bangladesh are operating their business in a highly competitive business environment. The main objectives of the study are to explore antecedents of Customer Loyalty and to develop a model of Customer Relationship Management for financial services industry especially for Private Commercial Banks (PCBs) in Bangladesh. To achieve the objectives, this study has looked into the available literature and conducted an empirical study on the causal relationships among different factors such as services quality, customer trust, customer perceived value, customer satisfaction, customer switching barrier, customer culture, and customer loyalty which are directly and indirectly related to CRM. A model has been developed based on comprehensive literature review, focus group discussion, and an extensive survey of the customers of some selected PCBs. The survey has been administered on 450 respondents with a structured questionnaire and the response rate has been 89.44%.In EFA, the study has explored seven factors which are related to CRM namely services quality, customer trust, customer perceived value, customer satisfaction, customer switching barrier, customer culture, and customer loyalty. Confirmatory Factor Analysis (CFA) has been performed to ensure the validity of the constructs. Except for one factor namely Customer Culture, all other factors have ensured the convergent and discriminant validity. The study has revealed that Customer Satisfaction is the most important determinant of Customer Loyalty whereas Services Quality, Customer Trust, and Customer Perceived Value act as significant antecedents of Customer Satisfaction. This study makes a significant contribution to the existing literature by showing the influences of different factors on Customer Loyalty and by developing a model of CRM in the financial service industry of Bangladesh.